2006
DOI: 10.1134/s0006297906040122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on synthesis of polyphosphates in Yersinia pseudotuberculosis and Listeria monocytogenes under starvation conditions

Abstract: It was found that at low temperature (6-8 degrees C) in the absence of nitrogen supply and at the presence of phosphate ions in the medium, Yersinia pseudotuberculosis and Listeria monocytogenes are able to actively synthesize reserve substances as polyphosphates. Most of the bacterial polyphosphates are alkali-soluble, especially at the preliminary stage of cell growth (lag-phase). This is proved by electron microscopic studies of ultrastructure of model microorganisms. During a long starvation period under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…One of the adaptation mechanisms for nutritional deficiency under suboptimal conditions of existence in bacteria is the synthesis of reserve substances [ 27 , 32 , 36 ]. In the cultures of Y. pseudotuberculosis that we studied, the ability to synthesize polyphosphates and poly- β -hydroxybutyric acid (PHBA) was found [ 30 ].…”
Section: Morphological Aspects Of the Y Pseudotuberculomentioning
confidence: 99%
See 2 more Smart Citations
“…One of the adaptation mechanisms for nutritional deficiency under suboptimal conditions of existence in bacteria is the synthesis of reserve substances [ 27 , 32 , 36 ]. In the cultures of Y. pseudotuberculosis that we studied, the ability to synthesize polyphosphates and poly- β -hydroxybutyric acid (PHBA) was found [ 30 ].…”
Section: Morphological Aspects Of the Y Pseudotuberculomentioning
confidence: 99%
“…It was established [25] that conformational changes in the structure of the active surface of enzymes, leading to an increase in catalytic activity which accelerates biochemical reactions in bacterial cells, underlie bacterial adaptation. Under the favorable trophic conditions, the ability of Y. pseudotuberculosis to accumulate reserve substances (β-hydroxybutyric acid, polyphosphates) and to consume them under fasting conditions has been proven [26,27].…”
Section: The Psychrophilicity Of Yersinia Pseudotuberculosis As a Fundamental Property Of Sapronoses Causative Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, PolyP is believed to be central to the survival strategies of certain modern bacteria. At low temperatures, when phosphate is available but nitrogen is scarce, Yersinia pseudotuberculosis and Listeria monocytogenes store the phosphate as PolyP for future use [ 35 ]. In the cyanobacterium, Aphanizomenon ovalisporum , the huge increase in DNA as dormant cells are formed probably depends on phosphate provided by PolyP bodies; this increase is believed to allow long-term survival during stress and a subsequent rapid resumption of metabolism and cell division when conditions improve [ 36 ].…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%
“…Several techniques can be used as methyl blue staining of poly-P (5). Buzoleva et al, (2006) demonstrated that most of the bacterial poly-P is alkali-soluble, especially at the preliminary stage of cell growth (21). Eixler et al, (2005) using several different methods for extraction of intracellular poly-P of Chlorella vulgaris and Synechocystic sp.…”
Section: Introductionmentioning
confidence: 99%